Clinical value of combined serum CA125, NSE and 24-hour urine VMA for the prediction of recurrence in children with neuroblastoma - Jinmin Li; Zilong Qi; Mo Chen; Jiachen Wang; Xiangyang Liu (BMC, 2023)
Abstract Background In this study, we intend to retrospectively analyze the clinical data of postoperative neuroblastoma children, including the results of follow-up examinations and laboratory tests, to explore the clinical value of combined serum Carbohydrate antigen 125 (CA125), neuron-specific enolase (NSE) and 24-hour urine vanillylmandelic acid (VMA) levels at baseline for the prediction of recurrence in children with neuroblastoma. Methods 265 children with neuroblastoma were successfully followed up, including 163 cases without recurrence (non-recurrence group) and 102 cases with recurrence (recurrence group). The levels of 24-hour urine VMA were determined using spectrophotometric methods. Additionally, the serum levels of CA125 and NSE were measured using electrochemiluminescence immunoassay. Results The serum CA125, NSE and 24-hour urine VMA levels were significantly higher in the recurrence group than in the non-recurrence group. It demonstrated a significant positive correlation between the levels of serum CA125, NSE, and 24-hour urine VMA in all children with neuroblastoma. All children in stage IV of neuroblastoma had the highest level of serum CA125, NSE and 24-hour urine VMA and vice versa. The combined CA125, NSE and VMA had significantly better sensitivity and specificity than an individual marker. Conclusions Combined serum CA125, NSE and 24-hour urine VMA had the potential to predict neuroblastoma recurrence more effectively.